Diversity of the Obligate Gut Bacteria Indicates Host–Symbiont Coevolution at the Population Level in the Plataspid Stinkbug Megacopta cribraria - Yuan Wang; Xiu‐Xiu Zhu; Bo‐Ren Xiao; Xin‐Rui Hou; Yu‐Xin Liu; Jia‐Yue Zhou; Yi‐Peng Ren; Wen‐Jun Bu; Huai‐Jun Xue (Ecology and Evolution, 2024)
ABSTRACT Ishikawaella is an obligate gut bacterium in stinkbugs that belong to Plataspidae family (Hemiptera: Heteroptera). It is vertically transmitted to newborn nymphs through capsules laid on eggs by maternal stinkbugs. Previous research has established a pattern of strict cospeciation between Plataspidae stinkbugs and Ishikawaella. However, the possibility of host–symbiont coevolution at the population level within Plataspidae stinkbugs has not been thoroughly explored. This study analyzed the samples of Megacopta cribraria from three phylogenetic clades to investigate host–symbiont coevolution in this insect species. We compared data from third‐generation sequencing (PacBio), next‐generation sequencing (Illumina), and first‐generation sequencing (Sanger), and the results indicated that Illumina sequencing most accurately represents the composition of gut bacterial communities. All stinkbug individuals shared a dominant amplicon sequence variant (ASV), which accounted for an average of 65.99% of Ishikawaella sequences (ranging from 58.68% to 87.01%). The top five ASVs (ASV0–ASV4) represented 99.82% of all Ishikawaella sequences. Among these, the number of base substitutions between any two ASVs ranged from 1 to 3, significantly lower than the number of substitutions between the main and minor ASVs. This finding suggests that closely related strains are likely to coexist in the same host. Beta diversity analyses revealed significant differences in Ishikawaella composition among the three phylogenetic clades, providing evidence for host–symbiont coevolution at the population level in Plataspidae stinkbugs.